Challenging Normal Science: An Interdisciplinary Approach to Jailed Individuals Self-Report of Lifetime and in-Jail Suicidal Ideations - Abderhalden, Frances P. (Crime & delinquency, 2022)
Suicidal behaviors are of critical public health concern. These behaviors are even more pervasive in the justice system, in particular in the correctional sector. Yet, the field of criminology has historically shown limited interest in furthering the scientific inquiry behind these behaviors. Interdisciplinary work has routinely been used as a buzz word in academia. This study argues that the intersection of criminology, psychology, and sociology are a beginning step to challenge normal science and progress into a new paradigm of scholarship, in relation to suicidology. The current study details the importance of knowledge building, exchange of theories, measurement, variables, and collaboration. Using real data to illustrate how this approach could work, a test of lifetime suicidal ideations and in-jail suicidal ideation is conducted to demonstrate the interdisciplinary nature of suicide within justice involved populations.